Tectonic setting, fluid inclusion and gold mineralization of the southwest Poli region (northern Cameroon Domain). (October 2022) - Ngounouno, Fadimatou Yamgouot; Negue, Emmanuel Nomo; Kolb, Jochen; Walter, Benjamin; Teda Soh, Arnaud Cedric; Patten, Clifford; Ngounouno, Ismaïla
Abstract: This paper documents original petrographic and structural data on metamorphic and magmatic rocks as well as the occurrence of gold mineralization in the Dourou Tchaga area (SW Poli) in the northwestern Cameroon domain. The study area is dominated by high-grade gneisses derived from a volcanic-sedimentary series alternating with orthogneiss and magmatic rocks. Four main deformation stages were distinguish comprising the early D1 and D2 deformations showing ductile behavior under amphibolite to granulite facies, followed by retrogression into greenschist facies. D3 and D4 are characterized by ductile-brittle and late brittle structures. Gold mineralization is hosted in laminated quartz veins in steeply dipping, ENE–WSW-trending, sinistral shear zone developed during D3 . Host rocks are high-grade metamorphic paragneiss and orthogneiss. Ore minerals include native gold, galena, sphalerite, pyrite and chalcopyrite; wall rock alteration assemblage includes stable pyrite, magnetite and hematite. This assemblage together with specific quartz microstructures indicate gold mineralization at lower greenschist facies conditions. Gold is disseminated in quartz veins and wall rock alteration zones, where it occurs as free grains but also as inclusions in pyrite and sphalerite. Two types of fluid inclusions are distinguished: aqueous-carbonic CO2 –H2 O and aqueous (H2 O), both with low to moderate (2.0–13.9 wt% NaCleq) salinity and variable CO2 content of 13–23 mole% for the aqueous-carbonic fluid inclusions. Fluid inclusions data and alteration assemblage provide evidence that gold precipitation in quartz veins occurred in response to an increase in fO2 caused by fluid pressure fluctuations in the shear zone. Gold mineralization in the northern Cameroon domain was formed during post-collisional stage and retrograde exhumation of the terrane in the greenschist facies toward the end of the Panafrican Orogeny.